KONFLIK PENGUASAAN TANAH PERKEBUNAN (Studi Kasus Antara PT Sumber Sari Petung Dengan Warga Masyarakat Kecamatan Ngancar, Kabupaten Kediri, Jawa Timur) - Erna Sri Wibawanti; Suswoto Suswoto (Kajian Hukum, 2017)
Conflict of land estates mastery between PT Sumber Sari Petung (PT SSP) and citizens of Ngancar Kediri with the background of the confidence of citizens in the three (3) villages, those are Babadan Village, Sugih Waras Village and Sempu Village Ngancar District that the land owned by PT SSP is the land which belongs to them, while PT SSP insisted that the land is theirs which is reinforced by the Right Granting Decree of BPN (SK. No. 28 / HGU / DA / 1074). This conflict began culminated with the release of the National Land Agency Decision No. 66 / HGU / BPN / 2000, which decided that the land that had been controlled by PT SSP area of 654.92 hectares of land declared as a state land and give the Cultivation Rights Title area of 3.842.760 M2 (three million eight hundred and forty-two thousand seven hundred and sixty meters square) to PT. SSP and the other 2.500.000 (250 Ha) is declared as an object of land reform. This conflict solution is initially done by approaches and discussions involving various parties. However, this method ultimately cannot resolve the conflict, and finally the solution is done through justice. In the judicial process, from the PTUN, the Civil Court to the Supreme Court ruling, all of them in favor of the PT SSP side. But the court ruling that already has a permanent legal force cannot be enjoyed by PT SSP, because BPN as the defeated party does not want to implement the ruling. Due to the absence of certainty, finally the completion  has been done again through  some case titles  by the Land Office from Kediri District. Finally, in 2011, PT SSP give up the land area of 250 hectares, to be released and declared as an object of Land reform which will be redistributed to farmers in three villages.